Diabetic Cardiovascular Neuropathy: Effects of Benfotiamine on Heart Rate Variability - Serhiyenko, Victoria A.; Hotsko, Marta E.; Serhiyenko, Alexandr (Challenges and Advances in Pharmaceutical Research Vol. 3, 2022)
The significance of cardiovascular autonomic neuropathy (CAN) has not been fully appreciated and there is no unified treatment algorithm. We aimed to evaluate the effects of benfotiamine (BFT) on the heart rate variability (HRV) in patients with type 2 diabetes mellitus (T2DM) and CAN. A total of 32 individuals with T2DM and a confirmed stage of CAN were randomly assigned to one of two therapy groups: Group 2 (n=17) got BFT 300 mg/d for three months in addition to normal antihyperglycemic medication. The parameters of heart rate variability (HRV) were studied. During the active and passive parts of the day, BFT was observed to lead to an increase in the sum of squares of differences between adjacent normal-to-normal intervals, as well as the high-frequency component of HRV. The beneficial effects of BFT suggest that it could be administered to people with T2DM and a confirmed stage of CAN.